2019
DOI: 10.1113/jp277452
|View full text |Cite
|
Sign up to set email alerts
|

Bladder overactivity and afferent hyperexcitability induced by prostate‐to‐bladder cross‐sensitization in rats with prostatic inflammation

Abstract: Key points There is clinical evidence showing that prostatic inflammation contributes to overactive bladder symptoms in male patients; however, little is known about the underlying mechanisms In this study, we investigated the mechanism that prostatic inflammation causes detrusor overactivity by using a rat model of chemically induced prostatic inflammation. We observed a significant number of dorsal root ganglion neurons with dichotomized afferents innervating both prostate and bladder. We also found that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 40 publications
6
68
0
1
Order By: Relevance
“…Intraprostatic formalin injection has been recognized as a convenient and qualified method to establish nonbacterial prostatic inflammation. Previous studies including ours showed that a single intraprostatic injection of 5% or 10% formalin could induce prostatic inflammation and result in bladder overactivity for up to 4 weeks, as well as bladder afferent hyperexcitability at 1 week after formalin injection . Our current study further confirmed that formalin‐treated rats exhibit bladder overactivity that lasts for 8 weeks using metabolic cage measurements and continuous CMG recordings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Intraprostatic formalin injection has been recognized as a convenient and qualified method to establish nonbacterial prostatic inflammation. Previous studies including ours showed that a single intraprostatic injection of 5% or 10% formalin could induce prostatic inflammation and result in bladder overactivity for up to 4 weeks, as well as bladder afferent hyperexcitability at 1 week after formalin injection . Our current study further confirmed that formalin‐treated rats exhibit bladder overactivity that lasts for 8 weeks using metabolic cage measurements and continuous CMG recordings.…”
Section: Discussionsupporting
confidence: 85%
“…Among these models, intraprostatic injection of chemicals (such as formalin, carrageenan, zymosan, or complete Freund adjuvant) is a convenient and effective approach. Our previous studies showed that a rat model of formalin‐induced prostatic inflammation developed molecular changes similar to those identified in human BPH specimens and exhibits 13 at 1 week after intraprostatic formalin injection . Schwartz et al also reported that bladder afferent pathways were sensitized in a 4‐week mouse model of prostatitis induced by intraprostatic zymosan injection possibly due to cross‐organ sensitization between the prostate and bladder.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The rat model of prostatic inflammation used in the present study is not a direct model of BPH; however, we have shown that this rat model exhibits the upregulation of androgen receptor-responsive genes and TGF-b-related genes in the prostate [16], which is similarly seen in human BPH tissue [19], and that increased interleukin-18 expression induced by inflammasome activation is similarly observed in the formalin-induced rat prostatic inflammation model [20] and in human BPH specimens with inflammatory cell infiltration [21]. Although prostatic inflammation is considered to be involved in development of BOO in patients with BPH [22], changes in voiding function in our model appear to be BOOindependent because we recently reported that there was no significant difference in the prostate weight between vehicleand formalin-injected rats, indicating that prostatic inflammation does not induce prostatic enlargement in the same model of prostatic inflammation [17]. Also, the rat prostate is anatomically positioned apart from the urethra and not surrounded by a capsular tissue [23]; therefore, prostatic enlargement, if any, is not likely to induce the BOO condition in rats; thus, the model of non-bacterial prostatic inflammation used in the present study seems useful to investigate inflammation-related events, other than BOO, in human BPH with tissue inflammation.…”
Section: Discussionmentioning
confidence: 68%
“…© 2019 The Authors BJU International © 2019 BJU International in rats with formalin-induced prostatic inflammation is dependent on activation of primary afferents in the pelvic nerve, which contain dichotomized afferents, because the transection of the pelvic nerve prevented bladder overactivity as well as upregulation of nerve growth factor in the bladder mucosa following prostatic inflammation [17]. It seems reasonable, therefore, to assume that activation of the pelvic nerve containing dichotomized afferents after prostatic inflammation alters the functional and molecular properties of the PGE2-EP4 system in the urothelium to induce bladder overactivity in the present study.…”
mentioning
confidence: 99%